Absolute risk assessment for guiding cardiovascular risk management in a chest pain clinic. Issue 6 (23rd February 2021) - Black, J Andrew; Campbell, Julie A; Parker, Serena; Sharman, James E; Nelson, Mark R; Otahal, Petr; Hamilton, Garry; Marwick, Thomas H
Abstract: Objectives: To assess the efficacy of a pro‐active, absolute cardiovascular risk‐guided approach to opportunistically modifying cardiovascular risk factors in patients without coronary ischaemia attending a chest pain clinic. Design: Prospective, randomised, open label, blinded endpoint study. Setting: The rapid access chest pain clinic of Royal Hobart Hospital, a tertiary hospital. Participants: Patients who presented to the chest pain clinic between 1 July 2014 and 31 December 2017 who had intermediate to high absolute cardiovascular risk scores (5‐year risk ≥ 8%). Patients with known cardiac disease or from groups with clinically determined high risk of cardiovascular disease were excluded. Main outcome measures: The primary endpoint was change in 5‐year absolute risk score (Australian absolute risk calculator) at follow‐up (at least 12 months after baseline assessment). Secondary endpoints were changes in lipid profile, blood pressure, smoking status, and body mass index, and major adverse cardiovascular events. Results: The mean change in risk at follow‐up was +0.4 percentage points (95% CI, –0.8 to 1.5 percentage points) for the 98 control group patients and –2.4 percentage points (95% CI, –1.5 to –3.4 percentage points) for the 91 intervention group patients; the between‐group difference in change was 2.7 percentage points (95% CI, 1.2–4.1 percentage points). Mean changes in lipid profile, systolic blood pressure, and smoking status were larger for the intervention group, but not statistically different from those for the control group. Conclusions: An absolute cardiovascular risk‐guided, pro‐active risk factor management strategy employed opportunistically in a chest pain clinic significantly improved 5‐year absolute cardiovascular risk scores. Trial registration: Australia New Zealand Clinical Trial Registry, ACTRN12617000615381 (retrospective).